MENINGKATKAN ETIKA PERGAULAN SISWA MELALUI LAYANAN INFORMASI DI KELAS X SMA NEGERI 2 KOTA BENGKULU - Rahmad hidayat; widya kartika sari (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2018)
This study aims to determine: 1) The level of etiquette students before being given the information service class B X IPS SMAN 2 Bengkulu City. 2) LEVEL tetika student association after being given the information service at IPS B class X SMA Negeri 2 Bengkulu City. 3) Is the information services can improve etiquette students in class X IPS B SMAN 2 Bengkulu City. The method used in this research is a class act. Subjects in this study the IPS B class X SMA Negeri 2 Kota Bengkulu.Prosuder classroom action research conducted through four (4) stages: 1) planning, 2) implementation, 3) observation, 4) reflection. Once the data is collected and analyzed obtained the following results: Tingkatetika association of students before being given the information service at IPS B grade X SMAN 2 Bengkulu City obtained an average score of 91 with a low category. The level of etiquette student after the given service information on IPS B grade X SMAN 2 Bengkulu City has increased by an average score of 123 in the high category. Service information is very effective for improving students about etiquette it is seemingly on the success rate of etiquette students before and after the given service information from one cycle, second cycle and third cycle has increased very significantly.